Comparative Effect of Calcium Mesoporous Silica Versus Calcium and/or Fluoride Products Against Dental Erosion - Canto,Fernanda Michel Tavares (2020)
Abstract The aim of this study was to compare the effects of a single application of a new calcium mesoporous silica nanoparticle (Ca2+-MSN) versus other calcium and/or fluoride products against dental erosion. Enamel blocks were half-covered and assigned to six groups (n = 10): Ca2+-MSNs; casein phosphopeptide-amorphous calcium phosphate mousse (CPP-ACP); CPP-ACP/F− (900 ppm F−); titanium tetrafluoride (TiF4 1%); sodium fluoride (NaF 1.36%); and Milli-Q® water (negative control). A single application for each product was completed on the exposed areas of the blocks and were submitted to an erosive challenge. Differences in volumetric roughness (Sa), and tooth structure loss (TSL) by use of three-dimensional noncontact optical profilometry were evaluate. Scanning electron microscopy (SEM) was performed. Analysis of variance and Tukey’s test for Sa and the Kruskal-Wallis and Mann-Whitney U tests (p< 0.05) for TSL, respectively. Results: When evaluating Sa, all products presented differences in roughness when compared with the control group (p< 0.05) but not with each other (p > 0.05). However, when analyzing the TSL, it was observed that Ca2+-MSNs, TiF4, and NaF were more effective in preventing dental erosion versus CPP-ACP, CPP-ACP/F−, and Milli-Q® water (p< 0.05). In the SEM images, the negative control presented the worst loss of dental structure, with more porous enamel. Ca2+-MSNs were as effective as TiF4 and NaF to reduce the tooth structure loss.